1991
DOI: 10.1002/jcp.1041490105
|View full text |Cite
|
Sign up to set email alerts
|

Caco‐2 cells cultured in serum‐free medium as a model for the study of enterocytic differentiation in vitro

Abstract: Caco-2 cells, which express spontaneous enterocytic differentiation at confluency, is one of the most relevant in vitro models for the study of differentiation and regulation of intestinal functions. However, these cells are normally cultured in the presence of 15-20% serum which renders extremely complex the identification of the factors involved in the regulation of both proliferation and differentiation. This study has been devoted to the establishment of chemically defined culture conditions which can sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(163 citation statements)
references
References 43 publications
10
150
1
2
Order By: Relevance
“…We took advantage of the ordered system of enterocyte differentiation to assess MLCK isoform expression, both in the in vitro Caco-2 cell model of enterocyte differentiation (21,30) and in vivo, as assessed in human intestine. Analysis of mRNA from Caco-2 cells and human intestinal epithelia showed that long MLCK expression was limited to isoforms 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…We took advantage of the ordered system of enterocyte differentiation to assess MLCK isoform expression, both in the in vitro Caco-2 cell model of enterocyte differentiation (21,30) and in vivo, as assessed in human intestine. Analysis of mRNA from Caco-2 cells and human intestinal epithelia showed that long MLCK expression was limited to isoforms 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content of each sample was quantified using the Biorad DC kit (Biorad, Hercules, CA). Caco-2 cells exhibit a constitutively high level of IAP activity 23,24 , so, we used this cell line as a positive control in our experiments.…”
Section: Intestinal Alkaline Phosphatase Activitymentioning
confidence: 99%
“…Intestinal Alkaline Phosphatase (IAP) is exclusively expressed in villus enterocytes in normal mucosa and hence serves as an excellent marker of crypt-villus differentiation 23,24 . The putative effect of normal LPL on epithelial differentiation was investigated using T84, a cryptlike intestinal epithelial cell line, co-cultured with freshly isolated normal LPL for 1 hour, 4 and 8 days (Fig 1A).…”
Section: Normal Lpl Induce An Increase Of Iap Activity In T84 Cellsmentioning
confidence: 99%
“…Because primary cultures of differentiated human Paneth cells are not yet well established, the intestinal epithelial cell line CaCo2 was used (Cario et al, 1999;Jumarie and Malo, 1991). In mitotic CaCo2 cells, immunoreactivity to Cnx was found in numerous dispersed cisternae and vesicles, a common phenomenon observed for proteins associated with the ER (Jesch and Linstedt, 1998).…”
Section: Discussionmentioning
confidence: 99%